Real-World Effectiveness and Safety of Ustekinumab for Ulcerative Colitis From 2 Tertiary IBD Centers in the United States. Issue 1 (5th February 2021) - Hong, Simon J; Krugliak Cleveland, Noa; Akiyama, Shintaro; Zullow, Samantha; Yi, Yangtian; Shaffer, Seth R; Malter, Lisa B; Axelrad, Jordan E; Chang, Shannon; Hudesman, David P; Rubin, David T
Abstract: Background: Ustekinumab has been recently approved for the treatment of moderately to severely active ulcerative colitis (UC). The registry trials for ustekinumab in UC demonstrated efficacy and safety, but data on real-world outcomes are limited. We describe the effectiveness and safety of ustekinumab in patients with UC from 2 US tertiary inflammatory bowel disease centers. Methods: Patients with moderately to severely active UC treated with ustekinumab at NYU Langone Health (New York, New York) and University of Chicago Medical Center (Chicago, Illinois) between January 2016 and March 2020 were retrospectively included. The primary outcome was clinical remission at 3 and 12 months, defined as a partial Mayo score of ≤2, with a combined rectal bleeding and stool frequency subscore of ≤1. Results: Sixty-six UC patients were included. Ninety-two percent of patients had prior exposure to biologics or tofacitinib. Forty-three percent and 45% of patients achieved clinical remission by 3 and 12 months, respectively. Anti-TNF nonresponse and endoscopic Mayo score of 3 were negative predictors of clinical remission. Thirty-three percent of those followed for a year achieved concurrent endoscopic and histologic healing, which was significantly associated with lower partial Mayo score ( P < 0.01) and lower stool frequency ( P = 0.02). Serious adverse events occurred in 4 (6%) patients (3 UC exacerbations, 1 vasculitis). Conclusions: In this cohort of mostly biologic-refractory UC patients, treatment with ustekinumab achieved remission in nearly half of them at 12 months, and was associated with an overall favorable safety profile. These results are modestly better than the pivotal trials. Lay Summary: Our real-world experience of ustekinumab for patients with moderate to severely active ulcerative colitis found rates of response, remission, endoscopic improvement, and safety to be similar to pivotal trials, confirming that ustekinumab is an effective and safe option for these patients.